Nonalcoholic fatty liver disease: scintigraphy in the diagnosis of steatohepatitis - Silva,Alessandro D'Avila da (2021)
SUMMARY OBJECTIVE: Nonalcoholic fatty liver disease is the most prevalent cause of chronic liver disease worldwide. Nonalcoholic steatohepatitis is associated with increased mortality rates due to the liver and cardiovascular diseases. The gold standard for discriminating nonalcoholic fatty liver disease activity and staging is the anatomopathological examination, which is an invasive method. In this regard, noninvasive methods, such as scintigraphy, have been under investigation. This study investigated the role of scintigraphy in the diagnosis of nonalcoholic steatohepatitis in obese patients with nonalcoholic fatty liver disease undergoing bariatric surgery. METHODS: Patients undergoing bariatric surgery and liver biopsy were prospectively included. 99mTc-phytate scintigraphy was performed to assess liver/spleen, spleen/heart, and liver/heart uptake ratios, while 99mTc-isonitrile scintigraphy assessed liver/heart ratio. To evaluate the presence of nonalcoholic steatohepatitis, the results of 99mTc-phytate scintigraphy and 99mTc-isonitrile scintigraphy were compared with the anatomopathological examination. RESULTS: Sixty-one patients with nonalcoholic fatty liver disease were allocated into two groups, namely, nonalcoholic steatohepatitis (n=49) and non-nonalcoholic steatohepatitis (n=12). The results of scintigraphic images obtained after the infusion of radiopharmaceutical 99mTc-phytate in liver/spleen, spleen/heart, liver/heart ratios and 99mTc-isonitrile liver/heart ratio presented no difference between groups with and without nonalcoholic steatohepatitis with an accuracy of 47.5, 37.7, 50.8, and 52.5%, respectively. CONCLUSION: Scintigraphy was not proven to be a useful method to differentiate patients with and without nonalcoholic steatohepatitis.